Case Report: A Case of Leukocyte Adhesion Deficiency, Type III Presenting With Impaired Platelet Function, Lymphocytosis and Granulocytosis - Yahya, Amal M.; AlMulla, Asia A.; AlRufaye, Haydar J.; Al Dhaheri, Ahmed; Elomami, Abdulghani S.; Al-Hammadi, Suleiman; Kailas, Lalitha; Vijayan, Ranjit; Souid, Abdul-Kader (Frontiers in Pediatrics, 2021)
Fermitin family homolog 3 (FERMT3), alternatively kindlin-3 (KIND3), is an integrin binding protein (of 667 residues) encoded by the FERMT3 gene. The molecule is essential for activating integrin αIIbβ3 (the fibrinogen receptor) on platelets and for the integrin-mediated hematopoietic cell (including platelets, T lymphocytes, B lymphocytes, and granulocytes) adhesion. Its defects are associated with impaired primary hemostasis, described as ‘Glanzmann’s thrombasthenia (MIM#273800)-like bleeding problem’. The defects are also associated with infections, designated as ‘LAD1 (leukocyte adhesion deficiency, type I; MIM#116920)-like immune deficiency’. The entity that joins the impaired primary hemostasis with the leukocyte malfunction has been termed ‘leukocyte adhesion deficiency, type III’ (LAD3, autosomal recessive, MIM#612840), representing a defective activation of the integrins β1, β2 and β3 on leukocytes and platelets. Here, we report a male toddler with novel compound heterozygous variants, NM_178443.2(FERMT3):c.1800G>A, p.Trp600* (a nonsense variant) and NM_178443.2(FERMT3):c.2001del p.*668Glufs*106 (a nonstop variant). His umbilical cord separated at about three weeks of age. A skin rash (mainly petechiae and purpura) and recurrent episodes of severe epistaxis required blood transfusions in early infancy. His hemostatic work-up was remarkable for a normal platelet count, but abnormal platelet function screen with markedly prolonged collagen-epinephrine and collagen-ADP closure times. The impaired platelet function was associated with reduced platelet aggregation with all agonists. The expression of platelet receptors was normal. Other remarkable findings were persistent lymphocytosis and granulocytosis, representing defects in diapedesis due to the integrin dysfunction. The natural history of his condition, structure and sequence analysis of the variations, and comparison with other LAD3 cases reported in the literature are presented.